Cost-Efficiency Trade-off of Silicon Solar Cells for use in Perovskite-Silicon Tandem Modules - Sofia, Sarah E.; Wang, Hao; Bruno, Annalisa; Buonassisi, Tonio; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2019)
We use techno-economic analysis to examine the potential of low-cost, lower-efficiency multi-crystalline silicon bottom cells in perovskite-silicon tandem solar cells, compared to high-efficiency, higher-cost mono-crystalline silicon cells. Two representative tandems, a low-cost and a high-efficiency device, are examined and compared based on levelized cost of electricity (LCOE) in current and future utility and residential systems. This analysis is then extended to explore the impact of top cell bandgap and top cell module cost, thus providing broader insight into the effect of variations and uncertainty in the properties of the perovskite top cell, as well as yielding implications for the use of other materials, such as cadmium telluride, in a tandem solar module. A clear case for the value of low-cost silicon for use as a silicon bottom cell is demonstrated.
CRIS-Team Scopus Importer:2022-06-05
Keywords: multi-junction; perovskite; silicon; tandem techno-economic